RESPONS PETERNAK SAPI PERAH TERHADAP PEMBUATAN YOGHURT SUSU SAPI DENGAN PENAMBAHAN PUREE UBI JALAR (Ipomea batatas) DI DESA GEDAWANG KECAMATAN BANYUMANIK KOTA SEMARANG (The Response of Dairy Cow Farmer’s to Cow’s Milk Yoghurt Production With The Additional Sweet Potatoes Puree (Ipomea batatas) In Gedawang Village Banyumanik District Semarang City) - ROSALIA ROSALIA; MUHAMAD RUSLIYADI; SUNARSIH SUNARSIH (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2022)
The objectives of the research were to find out: 1) the response of dairy cow farmers to cow's milk yogurt production with the addition of sweet potato puree; 2) the factors (age, education level, experience of breeding and intensity of extension) that affect the response of dairy cow farmers; 3) the effectiveness of extension and the effectiveness of behavior shift of dairy cow farmers. This research used one group pretest-posttest design and the sampling technique used was the saturated sample technique (census) so that 30 respondents were obtained. The results of data analysis showed that the response of dairy cow farmers inGedawang Village, Banyumanik District was in the "high" category. The variables of age, education level, experience of raising livestock, and intensity of extension simultaneously have a very significant effect on increasing the response of dairy cow farmers in making cow's milk yogurt with the addition of sweet potato puree, with a significant value of 0.000 (P<0.01). Meanwhile, the variable of breeding experience had no significant effect on the response of dairy cow farmers in making cow's milk yogurt with the addition of sweet potato puree. The effectiveness of extension was categorized as effective with a score of 82.17% and the effectiveness of behavior shift was categorized as effective too with a score of 68.52%.